As relações de gênero nas residências universitárias do Campus I da UNEB - Santana, Francine Melo Rosa Alves de (2019)
This study aimed to analyze, from a gender perspective, the experiences of young residents of University Residences in the Student Assistance policy of Campus I of the State University of Bahia (UNEB), highlighting advances in relation to expansion of rights and citizenship. Gender relations are understood as social constructions, have a material basis and represent the process of producing places of power, differences that shape, shape, install and act on the identities of men and women in the institutional spaces of society. This is a qualitative case study research based on dialectical historical materialism. It was held at UNEB Campus I, a multicampi institution, which has 29 departments in 24 cities in Bahia. The empirical field integrated the four student residences of this campus. The research universe consisted of male and female students, enrolled and active in the courses and under the condition of residents of these residences. Different sources of information subsidized the knowledge about the research object: literature review, gender disaggregated statistical bases on the profile of UNEB resident students and data collection through interviews, which were analyzed according to the analysis technique. content. The results showed that the interviewees had a trajectory marked by socioeconomic vulnerability. The research found that male and female characteristics, as cultural products, influence student trajectories. However, when gender and social class were related, it was noticed that young people from popular classes carried common marks of humiliation, suffering and invisibility. Regarding the permanence in the university, it was identified that the financial aid through the scholarship is the main source of income that keeps the interviewees in the university course. Access to the vacancy at the residence was, for most of the interviewees, marked by difficulties, a factor that demonstrates the need to expand these vacancies. Regarding gender issues, it was observed that some people may live with gender inequalities and not realize the existence of this situation, possibly by naturalizing the pattern of female subordination and discrimination related to gender and sexual orientation. It was also identified the insufficiency of specific actions developed for resident women, who in maternity situations may have their care compromised, as they cannot stay at home with their child. Despite identifying negative aspects of living in the residences, the interviewees stressed that the physical proximity of the residence with the campus and the social and affective bonds built are positive aspects associated with living in these spaces. The data reinforce the understanding that permanence can not be thought only by providing material resources, one should also consider the symbolic aspects of the student's life, including the expansion of psychosocial support. The university needs to take an active stance in building new gender relations within its space, which is first and foremost a place for academic, professional, critical and citizen education.